2013
DOI: 10.1177/1471301213488900
|View full text |Cite
|
Sign up to set email alerts
|

Medication management concerns of ethnic minority family caregivers of people living with dementia

Abstract: This qualitative study explored the medication management experiences of Australian ethnic minority family caregivers of people living with dementia. From the perspective of this group of caregivers, medication management was a source of stress resulting from the progressive loss of ability of care recipients to manage their own medications; the complexity of the medication regime and the caregiver's lack of trust of the care recipient to safely and effectively manage medications. Caregivers used various strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(137 citation statements)
references
References 27 publications
5
130
1
1
Order By: Relevance
“…First, the literature showed that care recipients’ cognitive impairment required caregivers’ hypervigilance and constant involvement in medication management. One study reported that caregivers of older adults with dementia often checked‐up on their care recipients' understanding of medication instructions from doctors (Gillespie, Harrison, & Mullan, ). Results also show that as changes occurred with the progression of dementia over time, medication management expanded to include reminding care recipients to take their medications, checking pillboxes, dispensing medications and monitoring side effects (Cotrell et al, ; While, Duane, Beanland, & Koch, ).…”
Section: Resultsmentioning
confidence: 99%
“…First, the literature showed that care recipients’ cognitive impairment required caregivers’ hypervigilance and constant involvement in medication management. One study reported that caregivers of older adults with dementia often checked‐up on their care recipients' understanding of medication instructions from doctors (Gillespie, Harrison, & Mullan, ). Results also show that as changes occurred with the progression of dementia over time, medication management expanded to include reminding care recipients to take their medications, checking pillboxes, dispensing medications and monitoring side effects (Cotrell et al, ; While, Duane, Beanland, & Koch, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experience indicates that this will generate sufficient data for an in-depth analysis from multiple perspectives [41, 42]. However, interviews will stop when theoretical saturation is reached.…”
Section: Methodsmentioning
confidence: 99%
“…14 While at least one study showed that the involvement of family caregiver is associated with better medication adherence, qualitative research on this topic indicates that assuming responsibility for medication management can be a major source of stress for dementia family caregivers. 12,15 Caregivers in two qualitative studies described frustration with working to avoid conflict and to address uncooperativeness with care recipients during medication administration, with caregivers in the study by While and colleagues poignantly emphasizing that these challenges persist despite the caregiver having adequate knowledge of the medication regimen. 12 This suggests that the problems faced by family caregivers of those with cognitive impairment are complex and unlikely to be addressed by standard nursing interventions like medication education or the use of reminder systems.…”
Section: Introductionmentioning
confidence: 99%